Spectrum of Autoimmune Diseases—Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS)—Clinical Case - Agnieszka Meller; Wioletta Pawlukowska; Karolina Machowska-Sempruch; Masztalewicz Marta (Medicina, 2023)
Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) syndrome is a rare inflammatory disease of an undetermined aetiology. The condition is characterised by a range of clinical manifestations generally associated with damage to brainstem structures, the cerebellum, with characteristic magnetic resonance imaging (MRI) findings. The main feature is a good clinical and radiological response to glucocorticosteroid (GCS)-based immunosuppressive treatment. The diagnosis of CLIPPERS is difficult and requires extensive differential diagnosis. A specific biomarker in serum or cerebrospinal fluid (CSF) for this disorder is currently unknown. The pathogenesis of CLIPPERS remains poorly understood and its nosological position has not yet been established. Whether CLIPPERS represents an independent, genuine new disorder or a syndrome in the course of diseases with heterogeneous aetiology and/or their precursor stages remains debatable and incompletely clarified. We present a case report of a patient who was diagnosed with CLIPPERS syndrome on the basis of her clinical and radiological features and by performing an extensive differential diagnosis. The patient has been under neurological follow-up for five years.